A hybrid organic–inorganic layered TiO2 based nanocomposite for sunlight photocatalysis. Issue 22 (15th February 2016) - Benavente, Eglantina; Maldonado, Carlos; Devis, Sindy; Diaz, Leslie; Lozano, Harold; Sotomayor-Torres, Clivia; González, Guillermo
Abstract : A novel hybrid nanocomposite constituted of single TiO2 nanosheets sandwiched between stearic acid self-assembled monolayers was synthesized and tested in the photodegradation of methylene blue under sunlight. Abstract : A novel hybrid nanocomposite constituted of single TiO2 nanosheets sandwiched between stearic acid self-assembled monolayers was synthesized and tested in the photodegradation of methylene blue under sunlight. The product showed better photocatalytic performance than anatase under similar conditions, which may be further improved through sensitization with cadmium sulfide.